Highlights of the initial planning meeting of the joint innovative project on in-service primary teacher education held on 26 August - 4 September 1980 at the University of the Philippines, Quezon City, Philippines.
A total of 29 participants from nine member countries attended: Bangladesh, India, Indonesia, Malaysia, Nepal, Papua New Guinea, the Philippines, Republic of Korea, and Thailand. The UNESCO Regional Office for Education in Asia and Oceania, in Bangkok, was represented by a specialist in new methods in teacher education. The meeting was held in view of developing a design for studying in the countries involved the status of in-service primary teacher education and the methods of evaluation used, leading to suggestions for improvement.
Keywords: Primary school teachers -- In-service training -- Asia -- Congresses; Elementary school teachers -- In-service training -- Asia -- Congresses; Primary school teachers -- In-service training -- Philippines -- Congresses; Elementary school teachers -- In-service training -- Philippines -- Congresses; Primary school teachers -- Rating of -- Asia -- Congresses; Educational evaluation -- Asia -- Congresses